THE EFFECT OF PROBIOTIC MILK IMMERSION ON BULK-FILL COMPOSITE RESIN DISCOLORATION - Al Dina Yanuarita; Isyana Erlita; Buyung Maglenda (FKG Unlam, 2019)
Backgrounds: Bulk-fill composite resin is a new type of composite resin that has the ability to absorb polymerization rays up to a depth of 4-5 mm in a single cure because of the modification in its components formation. The main cause of composite resin restorations failure is discoloration. Discoloration may occur due to extrinsic factors such as consuming food or drink which is rich in color and low pH, namely probiotic milk. Consuming probiotic milk for a long time will significantly increase the risk of composite resin discoloration. This significant discoloration eventually causes shorter resistance of restoration in oral environment regarding the decrease in aesthetic value. Objectives: To determine the effect of probiotic milk immersion on bulk-fill composite resin discoloration. Methods: This research was true experimental study with pretest-posttest with control group design that consisted of six groups in total of thirty six samples. Discoloration will be analyzed using digital analysis with the CIELAB method. Results: One-way ANOVA and Post-Hoc Games-Howell tests showed significant differences on bulk-fill composite resin discoloration after immersion in probiotic milk and distilled water (control) for 6, 12 and 18 hours (p<0,05). Only in the immersion groups of 6 hours and 12 hours probiotic milk did not have a significant difference on discoloration (p>0,05). Conclusion: There is an effect of probiotic milk immersion on bulk-fill composite resin discoloration.